Motivasi Kerja dan Pengaruhnya Terhadap Kinerja Islam Karyawan BRI Syariah KCI Surabaya Gubeng - Putri, Wednesdayanti Angelia; Prasetyo, Ari (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
Basically BRISyariahâs employee have different job motivations. Working on an IslamicÂ environment certainly at least a little or a lot will affected their job motives, so that finnaly, itÂ can be shown the Islamic performance employee. The aim of this research was to examineÂ job motivation of BRISyariah KCI Surabaya Gubengâs employee influance on their IslamicÂ performance whether the Islamic performance assessment was affected by theirÂ motivations.This research is quantitative research and uses linier regression analysis as analysisÂ model. The sample in this research was obtained by purposive sampling method. Based onÂ this method, there were 44 employees in accordance with the criteria of this researchâsÂ sample that was determined with a minimum work term of 3 months. The performanceÂ assessment was rated by each department manager where they were placed. DataÂ collected by distributing questionnaires about their job motivation to employees andÂ performance appraisal sheet to the manager.The results of the research indicate that job motivation influence on the IslamicÂ performance of BRISyariah KCI Surabaya Gubengâs employee.